Making transnational law work in the global economy: essays in honour of Detlev Vagts - Bekker, Peter H. F.; Dolzer, Rudolf; Waibel, Michael (Cambridge Univ. Press, 2010)
Introduction : a Festschrift to celebrate Detlev Vagts' contribtuions to transnational law / Pieter H.F. Bekker, Rudolf Dolzer and Michael Waibel -- Detlev Vagts and the Harvard Law School / William Alford -- Constructing and developing transnational law : the contribution of Detlev Vagts / Henry Steiner -- 'Hegemonic international law' in retrospect / Anthony Anghie -- Textual interpretation and (international) law reading : the myth of (in)determinacy and the genealogy of meaning / Andrea Bianchi -- The changing role of the state in the globalising world economy / Jost Delbrück -- Sources of human rights obligations binding the UN Security Council / Bardo Fassbender -- Is transnational law eclipsing international law? / Daniel Kalderimis -- Participation in the World Trade Organisation and foreign direct investment : national or European Union competences / Juliane Kokott -- From dualism to pluralism : the relationship between international law, European law and domestic law / Andreas Paulus -- Transnational law comprises constitutional, administrative, criminal and quasi-private law / Anne Peters -- Founding myths, international law, and voting rights in the District of Columbia / Siegfried Wiessner -- The tormented relationship between international law and EU law / Jan Wouters -- International law scholarship in times of dictatorship and democracy : exemplified by the life and work of Wilhelm Wengler / Andreas Zimmermann -- Sovereignty-plus in the era of interdependence : toward an international convention on combating human rights violations by transnational corporations / Olivier De Schutter -- The noisy secrecy : Swiss banking law in international dispute / Jean Nicolas Druey
Includes bibliographical references and index. - 30 Beitr. - Bibliographie von Detlev Vagts S. 655 - 661
Keywords: Vagts, Detlev F; Festschrift; Wirtschaftsrecht; Internationales Recht